If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4y + -23 = 10 + y Reorder the terms: -23 + 4y = 10 + y Solving -23 + 4y = 10 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -23 + 4y + -1y = 10 + y + -1y Combine like terms: 4y + -1y = 3y -23 + 3y = 10 + y + -1y Combine like terms: y + -1y = 0 -23 + 3y = 10 + 0 -23 + 3y = 10 Add '23' to each side of the equation. -23 + 23 + 3y = 10 + 23 Combine like terms: -23 + 23 = 0 0 + 3y = 10 + 23 3y = 10 + 23 Combine like terms: 10 + 23 = 33 3y = 33 Divide each side by '3'. y = 11 Simplifying y = 11
| 23+13x-15+5x-27x= | | 14000V=-2000t+20000 | | 5(9a)= | | 14000V=-2000+20000 | | -10x+14-8x+9= | | 3x-4(1-2x)=2x-(x+1) | | 2(a-b)= | | 3.7(-83x+-3)=3.7(7x+-30) | | (2x-1/2)^2=9/4 | | X+2x+4x+2=37 | | (13-6)x(12-3)+16= | | 3a^2+25+42=0 | | 9n=6 | | -49=.7y | | 2[5(4-1)]= | | x-4=169 | | t^2-19t+10=0 | | x^2y^2-2y=0 | | in(2x)-in(3x+2)=1 | | -8(w-3)=9w+41 | | (7x-9)(9x+9)=0 | | (49-12)/3 | | (2x-7)(9x+8)=0 | | 17=85 | | 17Xa=85 | | x+25=51 | | 3p^3+12p=0 | | 4(p+17.00)=53.50 | | 4p+17.00=53.00 | | 4p-17.0=53.00 | | 0.1x=0.35 | | 9x-2y/3*5z |